Aligning top-down and voluntary attention control across individuals - Gibson, Bradley S.; Trost, Jamie M.; Maxwell, Scott E. (Frontiers in Cognition, 2023)
Previous research has suggested that standard manipulations of top-down information in the spatial cueing paradigm do not elicit voluntary attention control across all participants (Gibson et al., 2023). Instead, this research showed that only about half of the individuals exhibited the expected pattern in which they reported feeling more agency when they performed visual search with the aid of an informative (arrow or onset) cue than when they performed this task with an uninformative cue or without any cue at all. The present study replicated these previous findings under conditions in which the standard manipulation of top-down information was conveyed by a number cue (as opposed to an arrow or onset cue). But more importantly, the present study also found that the proportion of individuals who aligned top-down and voluntary attention control could be increased to approximately 90% by combining the standard manipulation of top-down information with a novel manipulation of volition in a separate condition in which participants were given the opportunity to freely choose (or not) the direction of the spatial cue on each trial.Despite conceding experimental control of cued direction (but not cue validity) to participants in this latter condition, most participants (85%) nevertheless distributed their direction choices equally across the four directions. These findings suggest that providing participants active control of stimulus parameters may be required to elicit a strong sense of agency (and voluntary control) in the laboratory.